2015
DOI: 10.1680/geot.14.p.207
|View full text |Cite
|
Sign up to set email alerts
|

Modelling the seismic performance of rooted slopes from individual root–soil interaction to global slope behaviour

Abstract: Modelling the seismic performance of rooted slopes from individual root-soil interaction to global slope behaviour T. LIANG Ã , J. A. KNAPPETT Ã and N. DUCKETT † Many natural and man-made slopes are planted with vegetation, and it is known that this can increase the stability of slopes under static conditions. There is anecdotal evidence that vegetated slopes also perform better than fallow slopes during earthquakes. However, the study of the dynamic behaviour of slopes planted with species having dichotomous … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
50
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(54 citation statements)
references
References 20 publications
4
50
0
Order By: Relevance
“…The load displacement data also suggested that deep roots were mobilised and broken in sequence rather than simultaneously (see the numerous sudden small drops on the 75-mm curve, Fig. 9)-this has also been observed previously for straight (vertical) root analogues in large DSA tests (Liang et al 2015).…”
Section: Direct Shear Tests: Rar Effects Within Tap Root Systemsupporting
confidence: 84%
See 3 more Smart Citations
“…The load displacement data also suggested that deep roots were mobilised and broken in sequence rather than simultaneously (see the numerous sudden small drops on the 75-mm curve, Fig. 9)-this has also been observed previously for straight (vertical) root analogues in large DSA tests (Liang et al 2015).…”
Section: Direct Shear Tests: Rar Effects Within Tap Root Systemsupporting
confidence: 84%
“…Here, RAR was defined using the following equation Landslides where A r is the total root cross-sectional area and A is the area of CRZ (CRZ and ZRT are the same for the 3D root cluster) rather than the total cross-sectional area of the DSA. This was selected based on the previous observation of Liang et al (2015) that root influence on shearing properties is confined to an area local to the roots. Test series B utilised a simpler group of straight (vertical) root analogues at the same confining stress (8 kPa), such that the effect of root morphology could be investigated through a comparison with test series A.…”
Section: Testing Methodologymentioning
confidence: 99%
See 2 more Smart Citations
“…The model parameters have subsequently been validated against centrifuge test data (i.e. full-scale stresses) on the dynamic response of sandy slopes (Al-Defae et al, 2013;Liang et al, 2015) and buildings on shallow foundations during earthquake shaking. The use of the correlations in this paper allows for an additional validation to be made against 1g test data (to explore the stress dependency of stiffness) and for a static loading problem.…”
Section: Constitutive Modellingmentioning
confidence: 99%